If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -7x = 106 + -28x Solving 10 + -7x = 106 + -28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28x' to each side of the equation. 10 + -7x + 28x = 106 + -28x + 28x Combine like terms: -7x + 28x = 21x 10 + 21x = 106 + -28x + 28x Combine like terms: -28x + 28x = 0 10 + 21x = 106 + 0 10 + 21x = 106 Add '-10' to each side of the equation. 10 + -10 + 21x = 106 + -10 Combine like terms: 10 + -10 = 0 0 + 21x = 106 + -10 21x = 106 + -10 Combine like terms: 106 + -10 = 96 21x = 96 Divide each side by '21'. x = 4.571428571 Simplifying x = 4.571428571
| 5+7x=11+7x | | 20+5=24 | | 2x-36=100 | | 3(x+3)=(3x+9) | | 30=-11x | | (2x-3)(2x-3)=0 | | 5x-y+150=180 | | -N+(v*b*b)=r | | (x-2)(x+2)=(x-1) | | 2.6z^2-0.9z+2=0 | | m-1=2 | | 5x+12-13= | | 5h-2= | | 141-5x=3x+21 | | -9t-5=-4t+10 | | 6(Z-3)+7Z-3= | | 7x^2-27x-14=0 | | -3X+1=-8X-4 | | -32-4x=8-9x | | a-2=-a-5 | | 139-7x=29x+23 | | .0002x^2-.316x+127.9=7 | | 15y^2+28y+5=0 | | 8+8b=10b | | 13-9x=123-44x | | -16x^2+90x-60=0 | | 12=.50x-8 | | 8-(2x+4)=-2(x-1)+10 | | b+5=-(b+2) | | 2x^3(5x^3-7)= | | -9X+5=-4X-6 | | 8(n-6)=6-n |